1998
DOI: 10.1046/j.1365-2036.1998.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine bismuth citrate (RBC) based triple therapy for 7 days is more effective than RBC plus clarithromycin for 14 days in dyspeptic patients with Helicobacter pylori infection

Abstract: The 1-week treatment with RBC plus clarithromycin and tinidazole yielded higher eradication rates than the 2-week treatment with RBC plus clarithomycin. Both treatments were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…H. pylori eradication therapies based on RBC are markedly superior to those incorporating bismuth in the BC or BS formulations, and are about as effective as those incorporating proton pump inhibitors. Current 1 week RBC 44 –46 and proton pump inhibitor 47 triple therapies, for instance, typically achieved eradication rates better than 90%, compared with about 80% for classical 2 or 4 week BC and BS triple therapies 48 . The extent to which the inhibitory effect of RBC on the bacterial motor mechanism of H. pylori , revealed in our study contributes to the greater clinical effectiveness of RBC is difficult to quantify.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…H. pylori eradication therapies based on RBC are markedly superior to those incorporating bismuth in the BC or BS formulations, and are about as effective as those incorporating proton pump inhibitors. Current 1 week RBC 44 –46 and proton pump inhibitor 47 triple therapies, for instance, typically achieved eradication rates better than 90%, compared with about 80% for classical 2 or 4 week BC and BS triple therapies 48 . The extent to which the inhibitory effect of RBC on the bacterial motor mechanism of H. pylori , revealed in our study contributes to the greater clinical effectiveness of RBC is difficult to quantify.…”
Section: Discussionmentioning
confidence: 71%
“…However, decreased H. pylori motility in the presence of RBC should in theory suppress colonization, 4 –6 and in vitro occurs at concentrations of the agent and with an immediacy suggesting that this pharmacological action will be of clinical importance. The idea that immobilization of the bacterium has a clinical role in current H. pylori eradication therapies 44 –47 is further supported by our finding (data unpublished) that proton pump inhibitors also inhibit H. pylori motility in vitro ; at concentrations well below those needed for anti‐bacterial action 49 …”
Section: Discussionmentioning
confidence: 75%
“…When RBC is combined with two antimicrobials, the RBC-based triple therapy, it provides a higher ef®cacy of eradicating H. pylori and the therapy can be shortened to 7 days. 4,5 RBC-based triple therapy has also been shown to be comparable to proton pump inhibitor triple therapy in two studies using either omeprazole 6 or lansoprazole. 7 In vitro studies suggest that the use of RBC in combination with metronidazole SUMMARY Background: We have previously shown that ranitidine bismuth citrate (RBC)-based triple therapy is comparable to proton pump inhibitor-based triple therapy in eradicating Helicobacter pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…Dual compared with triple therapy: RBC triple therapy for one week has been compared with dual therapy combining RBC and clarithromycin for two weeks (Tables 1, 3 and 4) (34-37). One study (34) found one-week triple therapy with RBC 400 mg bid, clarithromycin 250 mg bid and tinidazole 500 mg bid to be significantly better (P=0.001) than two-week dual therapy with RBC 400 mg bid and clarithromycin 500 mg bid (34). However, in other studies using RBC and clarithromycin dual therapy for two weeks, the proportion of patients cured was equivalent to those using RBC, clarithromycin and metronidazole triple therapy for one (36) or two weeks (26,37).…”
Section: Eradication Of H Pylori Infectionmentioning
confidence: 99%